Population Dynamics, Ecology and Infection Rate in Freshwater Snails in Shelleng Local Government Area, Adamawa State, Nigeria - Na'acha, F.E. * , Naphtali, S.R. , Chessed, G. and Nassai, I. (Sokoto Journal of Medical Laboratory Science)
The research on population dynamics, ecology and  infection  rate  in  freshwater  snails  was carried out in Kiri dam and Shelleng  water bodies. Point A- Shelleng on GPS location N 9°54'17.78688” (Latitude) E 11°57'10.30284” (Longitude) and point B and C are on GPS location N 9°40'53.81508'' (Latitude) E 11°59'51.33408'' (Longitude). Monthly variation of physicochemical parameters was carried out from September 2018 to October 2019 and collection of snails was carried out to test for transmission dynamics of the snails. The snails were exposed to sunlight individually for 2 hours in a petri-dish that contains aged tap water. They were screened for cercarial shedding in the research laboratory under a dissecting microscope. There was significant difference between snail abundance and alkalinity; dissolve oxygen, pH and temperature of the water body and no significant difference between snail abundance with the turbidity and conductivity of the water. The highest abundance of snails was recorded in the month of June (20.5%) while the least was recorded in the month of December (2.5%). The infection rate of snails was (42.5%) of the 769 snails examined and B. truncatus had the highest infection (64.4%) while B. forskaii had the least infection (4.1%). The location of the study area has no effect on the distribution and abundance of snails but human activities and physicochemical parameters in this study supports freshwater snails.